2014
DOI: 10.3945/jn.114.197939
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Absorption and Tissue Utilization of Dietary Heme and Nonheme Iron Differ in Rats

Abstract: Elevated hepcidin significantly decreased heme- and nonheme-iron absorption but had a greater impact on nonheme-iron absorption. Differential tissue utilization of heme vs. nonheme iron was evident between erythroid and iron storage tissues, suggesting that some heme may be exported into the circulation in a form different from that of nonheme iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Proper heme levels are also crucial for normal fetal development, as defects can lead to limb deformities in addition to abnormal erythropoiesis (Keel et al, 2008). Not surprisingly then, increased circulatory hepcidin can have systemic effects; for example, decreasing heme-and nonhemeiron absorption to the duodenum (Cao et al, 2014). In the present case, the levels of hepcidin in the Nan/+ mouse are high enough to exert a physiological effect (Nemeth et al, 2004b).…”
Section: Discussionmentioning
confidence: 65%
“…Proper heme levels are also crucial for normal fetal development, as defects can lead to limb deformities in addition to abnormal erythropoiesis (Keel et al, 2008). Not surprisingly then, increased circulatory hepcidin can have systemic effects; for example, decreasing heme-and nonhemeiron absorption to the duodenum (Cao et al, 2014). In the present case, the levels of hepcidin in the Nan/+ mouse are high enough to exert a physiological effect (Nemeth et al, 2004b).…”
Section: Discussionmentioning
confidence: 65%
“…Iron utilization and bioavailability from the heme iron source was substantially higher than that observed for ferrous sulfate (nonheme iron) in both the pregnant and nonpregnant individuals (12)(13)(14). Furthermore, data from animal studies showed considerable differences in tissue deposition of the absorbed heme and nonheme iron tracers, suggesting that some heme may be exported into the circulation in a form different from that of nonheme iron (9). Data also support that there may be differential use of iron from heme and nonheme sources during pregnancy (65).…”
Section: Discussionmentioning
confidence: 92%
“…In humans, iron status is primarily regulated by the intestinal iron absorption of consumed external iron (8,9), as discussed elsewhere in these proceedings (10). Dietary iron is present in 2 forms: heme iron (animal flesh products) and nonheme iron (plants, some animal products, and supplements).…”
Section: Introductionmentioning
confidence: 99%
“…A diet generally contains heme iron (present in animal foods) with high bioavailability (15-35%) and non-heme iron (especially present in plantbased foods) with 1-20% bioavailability. 14 , 15 Heme iron generally constitutes only about 15% of the total dietary iron intake. 14 , 15 Two previous studies among blood donors did not find associations between intake of iron-rich food items and iron stores or Hb levels, 16 , 17 while one study among blood donors found mainly meat intake to be associated with iron stores.…”
Section: Introductionmentioning
confidence: 99%